ARTIFICIAL INTELLIGENCE TO IMPROVE ACCURACY AND EFFICIENCY OF PRESCRIBING BETWEEN DOCTORS & PHARMACISTS - Izzaty Zephaniah; Deny Febrian (Metacommunication: Journal of Communication Studies, 2023)
This qualitative method research aims to explain the use of artificial intelligence (AI) as an alternative means of optimizing interpersonal communication between doctors and pharmacists in terms of prescribing drugs. Because in practice, there are still many drug administration errors due to miscommunication between what the doctor writes or prescribes and what the pharmacist understands and gives to the patient. One that can be done by applying AI to electronic recipes. Unfortunately, the expansion of the use of AI technology in Indonesia in the pharmaceutical sector (especially drug prescribing) is still rarely found. In electronic prescribing, AI technology will help doctors to diagnose diseases suffered by patients through the analysis of previous medical reports. Then the doctor can directly send the prescription to the pharmacist through the computer. So that pharmacists can directly read, prepare and mix medicines. Through this mechanism, errors in prescribing that often occur can be minimized, thereby improving patient safety. The results of the study also show that although electronic prescribing can help overcome many medical problems, it can also cause new problems. For example electronic prescription systems can affect the workload of doctors and pharmacists by creating new types of prescribing errors such as delivery of prescriptions with medications, dosages or incorrect drug regimens. Not only that, but electronic prescribing systems can also raise concerns about information security and patient privacy when sharing prescription information with pharmacies. When sharing and storing patient prescription information, data security must be ensured to avoid changes that could potentially compromise the patient's health. The use of AI in electronic prescribing does not necessarily indicate clinical efficiency. Because it is also influenced by several factors, one of which is related to the knowledge and ability to use AI technology and the electronic prescribing system itself.